Effect of educational intervention on the use of personal protective equipment in nursing staff - Angeloni, Natália Liberato Norberto; Santos Junior, Aires Garcia dos; Ferreira, Adriano Menis; Valle, Lomberto Ariel Romeu; Lima, Krislley Crhistine de Almeida; Santos, Aline Romão dos; Lima, Helder de Pádua; Furlan, Mara Cristina Ribeiro; Maronesi, Maria Luísa Pereira (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: In the context of the COVID-19 pandemic, specific care in the use of Personal Protective Equipment (PPE) is crucial for patient care. Aim: To evaluate the impact of an educational intervention on the self-reported use of PPE by nursing professionals. The primary question guiding this research was: What is the effect of an educational intervention on the self-reported use of PPE by nursing professionals? Design: This quasi-experimental study used a before-and-after design and involved 98 nursing professionals. Results: It was found that 78.30% of nursing technicians reported absences from work due to COVID-19. Among these professionals, 82.27% reported having access to PPE during the pandemic, yet only 78.4% had received training on its usage. Notably, before the educational intervention, 53.2% of nursing technicians and 57.8% of nurses correctly performed PPE placement. After the intervention, these figures changed to 45.5% and 36.8%, respectively. Regarding the correct sequence of PPE removal, before the intervention, 32.9% of nursing technicians and 57.8% of nurses reported accuracy; these numbers slightly changed post-intervention to 34.1% and 52.6%, respectively. Implications: The educational intervention resulted in significant improvements in the correct removal of PPE, particularly among technical-level professionals. This outcome underscores the importance of ongoing training programs, tailored to the specific needs and experience levels of healthcare professionals, to enhance adherence to safety practices and optimize protection in high-risk environments.